Organisms for Development of SME in Algeria (مجلة الواحات للبحوث والدراسات, 2020)
In view of the key role played by SMEs in stimulating economic growth, the strong contribution to wealth generation, job creation, and as part of the policy of restructuring and upgrading SMEs in Algeria Which creates conditions both for the environment of these economic entities and for their functioning in the process of reviving industrial activities and their development, a range of support and support structures has been created, Principles and benefits differ. The aim of this article is to present the genesis of the various structures supporting Algerian SMEs. Key words-restructuring policy, upgrading, support structures, economic growth.